Prescription Pattern of Antihypertensives And Factors Associated With The Control of Blood Pressure Among Hypertensive Patients Receiving Care In A Nigerian Tertiary Hospital. - Onyinye, Ukoha-Kalu Blessing; Ogochukwu, Adibe Maxwell; Victoria, Ukwe Chinwe (International Journal of Scientific Research in Biological Sciences, 2020)
Hypertension undoubtedly is the leading cause of cardiovascular death worldwide. The study aimed to identify the prescription pattern of antihypertensive and factors associated with the control of blood pressure among hypertensive patients receiving care in a Nigerian Tertiary Hospital. The study was a retrospective cross sectional study carried out at the University of Nigeria Teaching Hospital Ituku/Ozalla, Enugu State Nigeria. A well Structured Pro-forma was used to extract variables from patient folders. These variables include Age, gender, marital status, religion, state of origin, educational level, occupation, Blood Pressure, age at first dose of antihypertensive, co-morbidities (diabetes, CKD), antihypertensive(s) used, duration of therapy, reasons for stopping (if stopped). Quantitative data was managed using Microsoft office excel and statistical product and services solution (SPSS) for windows. Continuous variables were expressed as mean ± SD and categorical variables as percentages with 95% confidence intervals. The students’t-test and the paired sample t-test were used to compare continuous variables while the pearson chi square test and fishers exact test will be used to compare categorical variables. All statistical test will be considered significant when the 2- sided p-value is <0.05.Three hundred and Ninety patient Folders were used for the study. About 174 (42.4%) of the patients were male while 216 (52.7%) were female with a mean age of 62 years. Amlodipine with a frequency of 182 (64%) was the most prescribed antihypertensive in this study followed by losartan 182 (46.43%) and the least being atenolol and nebivolol with frequency of 4 (1.03%) each. 302 (94.4%) patients had hypertension and an existing comorbidity while 88(22.6%) had no comorbidities. The most common comorbidities were diabetes mellitus and chronic kidney disease.About 197 (50.3%) of the patients had their blood pressure under control while 193(49.7%) had uncontrolled blood pressure. Age, Monthly income, educational status and presence of comorbidity were the major predictors of uncontrolled blood pressure. Amlodipine was the most frequently prescribed antihypertensive. About half of the patient had their blood pressure uncontrolled. Age and monthly income were associated with uncontrolled blood pressure.